Is the Climb Worth the View? The Savings/Alert Ratio for Reducing Vitamin D Testing - Hendrickson, Chase D.; McLemore, Michael F.; Dahir, Kathryn M.; Just, Shari; Shajani-Yi, Zahra; LeGrand, Joseph; Lehmann, Christoph U.; Weitkamp, Asli (Applied Clinical Informatics, 2020)
Background Despite guideline recommendations, vitamin D testing has increased substantially. Clinical decision support (CDS) presents an opportunity to reduce inappropriate laboratory testing.Objectives and Methods To reduce inappropriate testing of vitamin D at the Vanderbilt University Medical Center, a CDS assigned providers to receive or not receive an electronic alert each time a 25-hydroxyvitamin D assay was ordered for an adult patient unless the order was associated with a diagnosis in the patient's chart for which vitamin D testing is recommended. The CDS ran for 80 days, collecting data on number of tests, provider information, and basic patient demographics.Results During the 80 days, providers placed 12,368 orders for 25-hydroxyvitamin D. The intervention group ordered a vitamin D assay and received the alert for potentially inappropriate testing 2,181 times and completed the 25-hydroxyvitamin D order in 89.9% of encounters, while the control group ordered a vitamin D assay (without receiving an alert) 2,032 times and completed the order in 98.1% of encounters, for an absolute reduction of testing of 8% (p < 0.001).Conclusion This CDS reduced vitamin D ordering by utilizing a soft-stop approach. At a charge of $179.00 per test and a cost to the laboratory of $4.20 per test, each display of the alert led to an average reduction of $14.70 in charges and of $0.34 in spending by the laboratory (the savings/alert ratio). By describing the effectiveness of an electronic alert in terms of the savings/alert ratio, the impact of this intervention can be better appreciated and compared with other interventions.
Keywords: clinical decision support alerting; order entry; quality improvement; clinical practice guidelines; ambulatory care